Ex Situ Investigation of Surface Topography of Borax Crystals by AFM: Relation Between Growth Hillocks and Supersaturation Interpreted by Spiral Growth Theory - Suharso Suharso (Institut Teknologi Bandung, 2006)
The relationship between growth hillocks and supersaturation on the surface of borax crystals has been investigated using ex situ atomic force microscopy (AFM). The results showed that as the supersaturation increases, the mean step separation (yo) decreases. The mean step separation for the (010), (111), and (001) faces, at relative supersaturation (s-1) of 0.025 were 17.34 ± 0.56, 16.05 ± 0.24, and 17.4 ± 0.37 µm, and at relative supersaturation (s-1) of 0.21 were 11.43 ± 0.11, 8.23 ± 0.22, and 8.22 ± 0.31 µm, respectively. The average step height (h) of the (100) face for relative supersaturation of 0.025 and 0.21, was 109 and 76 nm, respectively. The edge free energy of the (010), (001), and (111) faces calculated at relative supersaturation (s-1) of 0.02 were 0.25, 0.23, and 0.25 J/m2 and calculated at relative supersaturation of 0.21 were 1.36, 0.98, and 0.98 J/m2 respectively.